Estimation of the best constant involving the L2 norm of the higher-order Wente problem - Sami Baraket; Makkia Dammak (Abstract and Applied Analysis)
We study the best constant involving the L2 norm of the p-derivative solution of Wente's problem in ℝ2p. We prove that this best constant is achieved by the choice of some function u. We give also explicitly the expression of this constant in the special case p=2.